PENGARUH PERENCANAAN PAJAK DAN PROFITABILITAS TERHADAP NILAI PERUSAHAANPADA PERUSAHAAN SUBSEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEKINDONESIA - Heri Enjang Syahputra; Desyana Desyana; Rosana Purba (JURNAL MUTIARA AKUNTANSI, 2022)
This study aims to determine: (1) the effect of tax planning partially on firm value in transportation sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019, (2) the effect of profitability partially on firm value in transportation sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019, and (3) the effect of Tax Planning and Profitability Simultaneously on Firm Value in Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2017-2019. The population in this study were all Transportation Subsector Companies Listed on the Indonesia Stock Exchange during the study period as many as 34 companies. The sample in this study were 16 Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange which were in accordance with the sampling criteria. Data collection methods used are documentation studies and literature studies. Classical assumption test used, including normality test, multicollinearity test. heteroscedasticity test, and autocorrelation test. The data analysis technique used is simple linear regression analysis and multiple linear regression.The results of this study indicate that tax planning partially has no effect on firm value. This is evidenced by the negative value of the regression coefficient, which is -0.106 and the tcount value is smaller than the ttable value, which is -0.122 < 1.67943 at a significance of 0.904 > 0.05. Profitability partially affects the firm value. This is evidenced by the positive value of the regression coefficient, which is 2.885 and the value of tcount is greater than ttable, which is 2.824 > 1.67943 at a significance of 0.007 < 0.05. Tax Planning and Profitability simultaneously have a positive effect on Firm Value. This is evidenced by the value of Fcount which is greater than Ftable, which is 4.025 > 3.20 at a significance of 0.025 < 0.05. The variation of the firm value variable is determined by the two independent variables, namely tax planning and profitability is 15.2%, while the remaining 84.8% is influenced by other variables not used in this study.